Knowledge, Attitude and Practice of radiation risk among employees in selected hospitals of Nepal (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Nepal is facing the problem of safe, effective and quality radiology services due to lack of adequate knowledge towards advance technology professionals. Therefore, the present study was designed to focus on the knowledge, attitude and practice on radiation among employee in selected hospitals.Material and Methods: This is a descriptive cross-sectional study conducted in among technical and non technical staff that were involved in or come across the radiology department. A set of self structured questionnaire and observation was used for data collection. Purposive sampling technique was used for the data collection. The collected data was compiled and analyzed by using SPSS 16.Results: The total number of staff participated in this study were 113, among them 65(58%) belong to technical group as health Professionals and 48(42%) belong to non -technical group. The knowledge of the technical staff was 66.95%, perception was 87.65% and the having the practice of protection was 75.9% whereas in non-technical staffs were 53.46%, perception is 64.60% and the having the practice of protection is 53.74%.Conclusion: The overall knowledge of radiation exposure amongst technical and non-technical staffs was average, poor perception and satisfactory practices. Regular training programmes and national legal law should be processed to reduce malpractice in radiations.Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 10-18